Effects of Probiotics on Diarrhea and CD4 Cell Count in People Living With HIV: A Systematic Review and Meta-Analysis - Zhang, Xiao-Li; Chen, Ming-Hui; Geng, Shi-Tao; Yu, Juehua; Kuang, Yi-Qun; Luo, Hua-You; Wang, Kun-Hua (Frontiers in Pharmacology, 2021)
It has been shown that gastrointestinal probiotics play an important role in maintaining intestinal bacteria homeostasis. They might be beneficial for people with Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) that remains a global health challenge. However, there is a controversy in the efficacy of probiotics in treating AIDS. This study systematically reviewed the evidence of the effects of existing probiotic interventions on AIDS, sought to provide information on the role of probiotics in HIV/AIDS patients. A meta-analysis identified by screening multiple databases was performed using a fixed-effects model using Review Manager 5.2 software. The meta-analysis showed that probiotics could reduce the incidence of AIDS-related diarrhea in the subjects (RR = 0.60 (95% CI: 0.44–0.82), p = 0.001). In addition, short-term use of probiotics (supplement time under 30 days) cannot reduce the incidence of diarrhea (RR = 0.76 (95% CI: 0.51–1.14), p = 0.19), while the long-term use of probiotics (supplement time over 30 days) can reduce diarrhea (RR = 0.47 (95% CI: 0.29–0.76), p = 0.002). Probiotics showed no effect on the number of CD4 cell counts among AIDS patients (MD = 21.24 (95% CI: -12.95–55.39), p = 0.22). Our data support that probiotics were associated with an obvious reduction in AIDS-related diarrhea, which is significant for additional research on this potential preventive strategy for AIDS.